2007
DOI: 10.1007/s00167-007-0362-4
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-year results of combined meniscal allograft transplantation, anterior cruciate ligament reconstruction and advancement of the medial collateral ligament

Abstract: The purpose of this study was to determine the objective and subjective long-term outcomes of the first free meniscal allograft transplantations in five patients with complete absence or non-repairable lesion of the medial meniscus after 20 years. Between 1984 and 1986 five patients underwent concomitant medial meniscal transplantation with a deep frozen meniscal allograft, ACL reconstruction and femoral advancement or temporary detachment of the MCL. The clinical outcome of the patients was evaluated 20 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 56 publications
1
46
0
5
Order By: Relevance
“…Além do mais, o quanto a restauração da dinâmica articular próxima da normal, proporcionada pelo transplante, possa prevenir a degeneração articular não está estabelecida. Trabalho (28) com seguimento de 20 anos de transplante de menisco mostrou que alguns pacientes isolados apresentaram resultados subjetivos satisfatórios, mas é preciso encarar o fato de que os resultados radiográficos mostram claramente que, em longo prazo, o transplante de menisco medial não protegeu a articulação do joelho das mudanças degenerativas. Contudo, os resultados são de difícil interpretação.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Além do mais, o quanto a restauração da dinâmica articular próxima da normal, proporcionada pelo transplante, possa prevenir a degeneração articular não está estabelecida. Trabalho (28) com seguimento de 20 anos de transplante de menisco mostrou que alguns pacientes isolados apresentaram resultados subjetivos satisfatórios, mas é preciso encarar o fato de que os resultados radiográficos mostram claramente que, em longo prazo, o transplante de menisco medial não protegeu a articulação do joelho das mudanças degenerativas. Contudo, os resultados são de difícil interpretação.…”
Section: Discussionunclassified
“…Contudo, os resultados são de difícil interpretação. Uma conclusão definitiva de que o transplante não protege contra artrite não pode ser embasada apenas em uma série de casos (28) . Assim, a experimentação animal é uma opção para se testar o transplante dentro de limitações estritas permitidas por um modelo experimental.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Studies with the longest follow-up focus on progression of radiological changes in the affected knee. These studies found a range from progression observed in all treated cases when using lyophilized and deep-frozen grafts [79], to progression evidenced in 59% of the cases with use of cultured viable grafts [47]. Verdonk et al wrote that surgeons may expect a chondroprotective effect of MAT in about 30% of patients [9], but this has to be further investigated in the coming years.…”
Section: Osteoarthritismentioning
confidence: 99%